Pengaruh Labelisasi Halal, Kualitas, dan Promosi Produk terhadap Volume Penjualan Sektor Industri Makanan pada UMKM Ponorogo - Mishela Dwiyanti; Febrilyantri, Candra (Prodi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Ponorogo, 2024)
Introduction: In the phenomenon of modern business competition, business people must have the ability to develop and maintain their business. Manufacturers must have strategies that companies can use to win competition in the business world. This condition ultimately encourages business actors to look for solutions and business strategies that can increase their competitiveness. However, there are still many MSMEs players who have not carried out active promotions, paid less attention to the quality in terms of packaging and food additives used, and have halal certification policies which they feel have not had an impact. Research Methods: The population in this research is MSMEs in the Halal Food Industry Sector with a sample size of 100 people. The sampling technique uses proportional stratified random sampling. Results: halal labeling has a significant effect on the sales volume of the Ponorogo MSMEs halal food industry sector. Quality has a significant effect on the sales volume of the Ponorogo MSMEs halal food industry sector. Promotions have a significant effect on the sales volume of the Ponorogo MSMEs halal food industry sector. Together they have a significant effect on the sales volume of the Ponorogo MSMEs halal food industry sector. The results of the coefficient of determination test (R2) show that halal labeling, quality and promotion influence sales volume by 54%, while the remaining 46% is influenced by other factors/variables outside this research. Conclusion: MSMEs in the food processing industry that have been certified halal in Ponorogo Regency to be able to maintance their commitment to halal labelling so that companies can continue develop.